Mencapai Strategic Fit Dalam Pengelolaan SDM : Transformasi Kebijakan SDM Dalam Menghadapi Dinamika Lingkungan Eksternal - Faridun Ni’am; Rauly Sijabat (EKSPOLHUM, 2026)
This article examines the urgency of achieving Strategic Fit between business strategy and Human Resource Management (HRM) systems as a critical driver of sustainable competitive advantage in a dynamic and uncertain business environment. This study employs a qualitative approach using a systematic literature review of more than 20 reputable scholarly articles related to strategic HRM, strategic fit, and HR transformation. The analysis focuses on vertical fit between organizational strategy and HRM policies and practices. The findings reveal that Strategic Fit is a dynamic and continuous process rather than a static alignment. Effective HRM–strategy alignment enables organizations to address skill gaps, strengthen organizational culture, and enhance long-term organizational performance. This study is limited to conceptual analysis based on secondary data. Future research should empirically test the proposed relationships using quantitative or multi-sector case study approaches. The results provide guidance for managers in designing adaptive HRM systems aligned with strategic objectives to respond effectively to environmental change. This study contributes by positioning Strategic Fit as an ongoing HR transformation process supported by competency development and organizational culture